How a COVID-19 positive patient can present to an otolaryngologist, a variable presentation: what not to miss? - Maqbool, Tabish; Mehta, Kulvinder Singh; Mustafa, Hena (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: COVID-19 has led to the global pandemic which started in Wuhan, in China. It is highly contagious and the presenting symptoms may not alarm the patient or the doctor and can be confused with allergies and other simple viral respiratory tract infections in mild cases. Aim of this study was to evaluate the various presentations of COVID-19 patients in department of otorhinolaryngology. Methods: This study was done during pandemic, from March 2020 to May 2020 for a period of 3 months in government medical college Srinagar. If the patient had any significant travel or contact with the known or suspected COVID-19 positive patient and the various ENT symptoms with which COVID positive patients presented, to the department were evaluated. Results: Majority of patients were males between the age group of 21 to 40 years. The most common symptoms encountered was cough and fever followed by sore throat and rhinitis. One patient also presented with subacute thyroiditis and two others as neck abscess. Two patients presented with sudden sensorineural hearing loss. Conclusions: Patients in the department can present with mild respiratory tract infection or also with some peculiar symptoms of subacute thyroiditis or abcess. So, careful history is the key to recognize these patients. And it is highly recommended that doctors during addressing the patients should be in proper protective kits to avoid contracting the disease.